Hepatic zonation determines tumorigenic potential of mutant β-catenin - Alexander Raven; Kathryn Gilroy; Hu Jin; Joseph A. Waldron; Holly Leslie; June Munro; Holly Hall; Rachel A. Ridgway; Catriona A. Ford; Doga C. Gulhan; Nikola Vlahov; Megan L. Mills; et al. (Nature, 2026)
Abstract Oncogenic mutations in phenotypically normal tissue are common across adult organs 1,2 . This suggests that multiple events need to converge to drive tumorigenesis and that many processes such as tissue differentiation may protect against carcinogenesis. WNT–β-catenin signalling maintains zonal differentiation during liver homeostasis 3,4 . However, the CTNNB1 oncogene—encoding β-catenin—is also frequently mutated in hepatocellular carcinoma, resulting in aberrant WNT signalling that promotes cell growth 5,6 . Here we investigated the antagonistic interplay between WNT-driven growth and differentiation in zonal hepatocyte populations during liver tumorigenesis. We found that β-catenin mutations co-operate with exogenous MYC expression to drive a proliferative translatome. Differentiation of hepatocytes to an extreme zone 3 fate suppressed this proliferative translatome. Furthermore, a GLUL and Lgr5 -positive perivenous subpopulation of zone 3 hepatocytes were refractory to WNT-induced and MYC-induced tumorigenesis. However, when mutant CTNNB1 and MYC alleles were activated sporadically across the liver lobule, a subset of mutant hepatocytes became proliferative and tumorigenic. These early lesions were characterized by reduced WNT pathway activation and elevated MAPK signalling, which suppresses zone 3 differentiation. The proliferative lesions were also dependent on IGFBP2–mTOR–cyclin D1 pathway signalling, in which inhibition of either IGFBP2 or mTOR suppressed proliferation and tumorigenesis. Therefore, we propose that zonal identity dictates hepatocyte susceptibility to WNT-driven tumorigenesis and that escaping WNT-induced differentiation is essential for liver cancer.